Pandangan Islam tentang Feminisme dan Kesetaraan Gender dalam Al-Qur’an - Agniya Rihadatul Aisy; Alya Shafira Octaviani; Aslaa Nabiilah; Asma Sabrina Nurain; Asep Abdul Muhyi (Gunung Djati Conference Series, 2023)
Islamic scholars and specialists never cease to find the phenomenon of feminism an interesting subject of research. Islam views feminism as a movement carried out by women who want equal rights as a creation of Allah SWT. This study aims to find out how Islamic views in the Quran about feminism and gender equality. This study uses the method of tafsir maudhu'i to examine the asbabun nuzul and plausibility of the verses studied. There are five steps, namely determining the theme studied, collecting verses related to the theme, looking for asbabun nuzul and plausibility from these verses. Research findings found that in Islam the position of women and men is equal.